The Maxwell rule in phase-transitions (Archives of Mechanics - Test, 1998)
The Maxwell rule, also known as the rule of equal areas, represents a basic notion in the phase transition processes. Although the rule might need amending for solids, it is treated as unquestionable for fluids. This belief relies on a thermodynamical argument. Namely, that the Gibbs thermodynamical potential should remain stationary during the transition process. Surprisingly, from the same thermodynamical argument, the Maxwell rule can be invalidated, even for fluids. Nonetheless, a revised form of the rule can be proposed.